Evolution of the consumption of lorazepam in a rural environment in the Region of Murcia (2012-2018) - Juan Antonio Cano-Hernández; Pura Ballester; Sandra Sierra-Alarcón; Alejandro Galindo-Tovar (Fundación Pharmaceutical Care España, 2022)
Objective: To evaluate the consumption of lorazepam in the Region of Murcia, specifically in the district of Mula, during the period 2012-2018, considering age and sex variables. Method: Cross-sectional descriptive study, where the use of benzodiazepines in a specific population during the period 2012 - 2018 is investigated. The variables collected were sex, age and the prescribed Defined Daily Dose. The data correspond to the dispensations of Lorazepam in the pharmacy offices of the disctrict of Mula, provided by the Health Assistance General Directorate. Daily dose per inhabitant and per 1000 inhabitants were calculated and the groups median and interquartile ranges were established p25 and p75 for later comparisons. Results: Overall consumption over the period increased by 0.42%. In men it increased by 21.4%, while in women it decreased by 7.5%. However, in women, consumption was at higher doses, betwand significant differences were found in lorazepam consumption een groups when analyzed by sex. The analysis by age showed a significant increase in consumption as the age of the patients increased. Conclusion: The consumption of benzodiazepines is high with increasing age, more so in women, and this may have an impact on the adverse effects associated with this group of drugs and present an important public health problem.